2014
DOI: 10.1016/j.apacoust.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and control strategies of aircraft noise in China

Abstract: Aircraft noise pollution is a common challenge faced by the world. In China, this problem has drawn more and more attention from the local government and general public, as the average growth of aviation capacity exceeds 10% every year. Therefore this review paper aims to investigate the characteristics of China's aircraft noise, the underlying reasons for noise complaints, and the negative impacts of aircraft noise on human health. It is found that there is an increase, on average, of 3% hearing loss per expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…They revealed that the increment of flight capacity and airport expansion could cause the growth of areas and populations annoyed by the noise. In the results of the study, they suggested several active and passive noise control such as purchasing noise detection equipment, installing sound insulation in residential buildings surrounding the airport, directing the airport expansion far away from the local community, and improving preventive legislation in China on aircraft noise control [23]. The interesting study conducted by Pamies, et al [24] proposed an active noise control on aircraft with bottom hinge window openings that can reduce sound transmission by 3 dB(A).…”
Section: Noise Control On the Aircraft Noisementioning
confidence: 99%
See 2 more Smart Citations
“…They revealed that the increment of flight capacity and airport expansion could cause the growth of areas and populations annoyed by the noise. In the results of the study, they suggested several active and passive noise control such as purchasing noise detection equipment, installing sound insulation in residential buildings surrounding the airport, directing the airport expansion far away from the local community, and improving preventive legislation in China on aircraft noise control [23]. The interesting study conducted by Pamies, et al [24] proposed an active noise control on aircraft with bottom hinge window openings that can reduce sound transmission by 3 dB(A).…”
Section: Noise Control On the Aircraft Noisementioning
confidence: 99%
“…Several diseases occurred by the aircraft noise such as hypertension, cardiovascular, and sleeping disturbance were most prevalent problems that needed to be both anticipated and decreased. In addition, studies conducted by several researchers have revealed active and passive noise control in buildings [23][24][25]. As the means of aviation capacity growths by 10% every year in China and at about 3% hearing loss exposure to aircraft noise, Xie et al [23] observed the aircraft noise impact to the psychological system and cardiovascular in human.…”
Section: Noise Control On the Aircraft Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Note that the L max descriptor is more understandable for community than any equivalent noise level or index. In various adopted metrics [5,9,10] and in going on investigations these descriptors are also widely used in combinations with other parameters such as number of flight events [11][12][13][14][15] and duration of noise events [12]. However, the common metric for various noise situations has not been yielded till now.…”
Section: Introductionmentioning
confidence: 97%
“…Also the prior existence of airports has not prevented an expansion of building and residential areas nearby, that may have arrived later, but still claim the same rights. In addition there may be cultural differences between nations, regions and local communities [337][338][339][340][341][342][343][344][345]. Such claims cannot be easily ignored, since they can be enforced by court orders.…”
Section: Variability Of Circumstances and Individualsmentioning
confidence: 99%